2021
DOI: 10.1111/jfbc.13833
|View full text |Cite
|
Sign up to set email alerts
|

Prospecting medicinal properties of Lion's mane mushroom

Abstract: Hericium erinaceus (Bull.) Persoon, a popular medicinal edible mushroom, owns a long history of usage in traditional Chinese medicine and also in other oriental countries. Along with this, its several bioactive compounds have been evolved into food supplements. Meanwhile, this present investigation aimed at extracting bioactive components from fruiting bodies of H. erinaceus using two different solvents and evaluating its in vitro antioxidant, antimicrobial, and antiproliferative efficacy. Chemical analysis sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 38 publications
0
5
0
Order By: Relevance
“…Comparing the results, this does not seem to be the case, since the lion’s mane contained the highest amounts of lutein and total carotenoids. Previous studies reported amounts of 47.81 μg/g and 45.98 μg/g of β-carotene in methanolic and ethanolic extracts, respectively, for lion’s mane mushroom ( Ghosh et al, 2021 ). This is not consistent with the present results, where β-carotene was not detected.…”
Section: Resultsmentioning
confidence: 95%
“…Comparing the results, this does not seem to be the case, since the lion’s mane contained the highest amounts of lutein and total carotenoids. Previous studies reported amounts of 47.81 μg/g and 45.98 μg/g of β-carotene in methanolic and ethanolic extracts, respectively, for lion’s mane mushroom ( Ghosh et al, 2021 ). This is not consistent with the present results, where β-carotene was not detected.…”
Section: Resultsmentioning
confidence: 95%
“…The vitamin C content was analyzed referring to Ghosh’s method [ 21 ]. F. velutipes (2.0 g) was added to 5 mL of an oxalic acid−EDTA solution and ground into a homogenate in an ice bath.…”
Section: Methodsmentioning
confidence: 99%
“…Commonly known as Lion’s Mane Mushroom, H. erinaceus is frequently used in traditional medicine, due to several health benefits such as anti-inflammatory, antibacterial or anticancer properties [ 50 ]. H. erinaceus extracts are commercialized as dietary supplements.…”
Section: Mushrooms In Alzheimer’s Diseasementioning
confidence: 99%